Explicit 3D functional dimensioning to support design intent representation and robust model alteration. Issue 1 (2nd January 2016) - Mandorli, Ferruccio; Otto, Harald E.; Raffaeli, Roberto
ABSTRACT: Design intent representation is a well-known issue in the MCAD domain, and is related to the readability, alterability, and usability of CAD models. The recent widespread introduction of functionality and commands in modern CAD systems, aimed at facilitating explicit modeling, introduces not only a new modeling paradigm supplementary to the feature-based approach, but also a new perspective on how the design intent can be captured and represented. Taking into account the traditional method of communicating design intent with functional dimensioning in mechanical drawings, in this paper a novel approach is presented, aimed at translating this traditional design intent representation from 2D into 3D. Objectives are directed towards the specification and implementation of dimensioning correspondence mapping and the identification as well as examination of shortcomings in current systems. This should help direct future improvements aimed at supporting 3D dimensioning within 3D explicit modeling systems. GRAPHICAL ABSTRACT: